Amitav Ghosh's The Shadow Lines: Re-Reading its Craft and Concerns. - Prasad, urari (Asiatic: IIUM Journal of English Language & Literature, 2008)
In this essay I examine Amitav Ghosh's craft and concerns in one of his finest novels, The Shadow Lines (1988). I further explore Ghosh's organisation of the diegetic elements, such as the novel's world and situation, events and characters, as well as the mode of telling and recounting the story, and argue how it is designed in conjunction with his central thematic preoccupation. As memory provides the narrative trigger in this novel, I analyse Ghosh's mnemonic enterprise as part of his narrative management. By using different narrative terms derived from Russian Formalism and Structuralist mediations, the novel's construction is taken apart to demonstrate Ghosh's innovative art. Besides dealing with the novel's narratological technique, this essay looks at Ghosh's interrogation of cartographic determinations against the background of Bengal's vivisection into East Pakistan (now Bangladesh) and West Bengal and evaluates his espousal of secular tolerance and alternative cartography in a multi-cultural scenario.